AUTHENTICITY, IDENTITY AND SUSTAINABILITY IN POST-WAR IRAQ: Reshaping the Urban Form of Erbil City - Ibrahim, Rebwar; Mushatat, Sabah; Abdelmonem, Mohamed Gamal (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2014)
Issues of authenticity and identity are particularly significant in cities where social and cultural change is shaping active transformation of its urban fabric and structure in the post-war condition. In search of sustainable future, Iraqi cities are stretched between the two ends of the spectrum, authentic quarters with its traditional fabric and modern districts with their global sense of living. This paper interrogates the reciprocal influences and distinct qualities and sustainable performance of both authentic and modern quarters of Erbil, the capital of the Iraqi province of Kurdistan, as factors in shaping sustainable urban forms for Iraqi cities. In doing so, the paper, firstly, seeks to highlight the urban identity as an effective factor in relation to sustainable urban form. Secondly, the city of Erbil in Iraq has been chosen as a field study, due to its regional, social, political and historical role in the region. Thirdly, the study emphasises the dynamic activities and performance of residential projects according to rational sustainable criteria. The research concludes that urban identity and the sense of place in traditional and historical places should inform design strategies in order to achieve a more sustainable urban context.